UBC9 overexpression promotes proliferation and metastasis in gastric cancer via ATF2 - QingShui Wang; ShengZhao Li; YiNing Xu; Yuluo Chen; Chao Xu; QiuYan He; Yan Ye; YiMin Huang; Yue Wu; KeJia Guo; YaJuan Wei; Yide Huang; et al. (World Journal of Surgical Oncology)
Abstract Gastric cancer remains a leading cause of cancer-related mortality worldwide, characterized by poor prognosis due to its aggressive nature and high metastatic potential. While the E2-conjugating enzyme UBE2I (UBC9), essential for SUMOylation, has been implicated in various cancers, its precise role in gastric cancer remains poorly understood. In the study, we demonstrate significant UBC9 overexpression in gastric cancer tissues, which correlates with poor clinical outcomes. Functional analyses revealed that UBC9 knockdown significantly suppressed gastric cancer cell proliferation, migration, and invasion in vitro and in vivo, whereas UBC9 overexpression enhanced these malignant phenotypes. Through integrated transcriptomic and proteomic analyses, we identified ATF2 (Activating Transcription Factor 2) as a crucial downstream effector of UBC9-mediated oncogenic signaling. The mechanistic relationship between these factors was confirmed as ATF2 knockdown substantially attenuated the oncogenic effects of UBC9 overexpression. This newly identified UBC9-ATF2 regulatory axis promotes gastric cancer progression by enhancing cellular proliferation and metastatic potential. Our findings establish UBC9 and ATF2 as promising prognostic biomarkers and potential therapeutic targets, suggesting that intervention in the UBC9-ATF2 axis may provide novel therapeutic strategies for inhibiting gastric cancer progression and improving patient outcomes.